Using git metrics to measure students' and teams' code contributions in software development projects - Hamer Campos, Sivana Alexa (2021)
Many software engineering courses are centered around team-based project development. Analyzing the source code contributions during the projects’ development could provide both instructors and students with constant feedback to identify common trends and behaviors that can be improved during the courses. Evaluating course projects is a challenge due to the difficulty of measuring individual student contributions versus team contributions during the development. The adoption of distributed version control systems like git enable the measurement of students’ and teams’ contributions to the project.In this work, we analyze the contributions within eight software development projects,with 150 students in total, from undergraduate courses that used project-based learning. We generate visualizations of aggregated git metrics using inequality measures and the contribution per module, which offer insights into the practices and processes followed by students and teams throughout the project development. This approach allowed us to identify inequality among students’ contributions, the modules where students contributed, development processes with a non-steady pace, and integration practices rendering a useful feedback tool for instructors and students during the project’s development. Further studies can be conducted to assess the quality, complexity, and ownership of the contributions by analyzing software artifacts.